ANALISIS PERBANDINGAN KINERJA KEUANGAN KOMPREHENSIF PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA (BEI) SEBELUM DAN SAAT PANDEMI COVID-19 - Ariska Devi Agustin Suhariani; Marhaendra Kusuma; Rike Selviasari (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
Food and beverage sector companies are one of the industries that have positive growth compared to other sectors. This research aims to determine comprehensive financial performance comparisons based on profitability ratio analysis with indicators of Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM) between the period before and during the pandemic.The research method used in this research is quantitative with secondary data obtained from the Indonesia Stock Exchange (IDX) with observational data carried out annually, namely from 2018 to 2021 which was carried out on 14 food and beverage companies. Data analysis was carried out using the Paired Sample T-test.The results of research related to the Different Paired Sample T-test on Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) generally show that there are significant differences before and during the pandemic.